Licensed professions: a new look at the association between social origins and educational attainments in Italy - Ruggera Lucia (SPRINGER, 2022)
It has long been known that Italy is characterized by the highest levels of professional regulation in Europe, but little attention has been given to the link between professional regulation and educational stratification. This article investigates the association between social origins and education by focusing on fields of study within tertiary education and by disaggregating the upper class of social origin into different micro-classes of professionals. Thus, since these professions are regulated in the first place by educational fields of study, it assesses how processes of social closure enhance occupational intergenerational immobility in the professional employment in Italy. Recently, deregulation of liberal professions in Italy has been central in many public and political debates. It contributes to these debates by examining the micro-level dynamics in the professionals' social reproduction and related practises of social exclusion, which may have strong implications for policy interventions. By using ISTAT's "Sbocchi Professionali dei Laureati" survey (2011), and employing multinomial logistic regressions, it shows how social selection into highly regulated fields of study is guided by parents' professional domain. The analyses indicate that both sons and daughters of licensed professionals are more inclined to graduate in a field of study that is in line with the father's profession and that this propensity is stronger among children of regulated self-employed professionals.